[On the right track-LRT ; It's time ; Police bill [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Tackles Light Rail Transit as a solution to the lack of public transportation; interview with L. Reyes about her jazz singing; and the controversial issue of the abolition of the Philippine Constabulary.